2003
DOI: 10.1515/cclm.2003.010
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipid Composition and LDL Oxidation

Abstract: Low-density lipoprotein (LDL) oxidation in vivo depends on lipid composition and on plasma antioxidant status. The aim of our study was to investigate the relationship between plasma lipid composition and LDL oxidation and, in particular, to explore whether LDL-cholesterol/triglycerides ratio (LDL-C/TG) and LDL-cholesterol/high-density lipoprotein (HDL)-cholesterol ratio (LDL-C/HDL-C) can be used as predictive parameters of LDL oxidation in vivo. In 87 volunteers over a wide range of age plasma lipids and LDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 26 publications
4
36
1
2
Order By: Relevance
“…The present results on increased LDL-C/TG and LDL-C/ HDL-C ratios in animals exposed to cold are indicative of LDL oxidation in vivo with the former ratio being suggested as an important predictor of LDL oxidation (Brizzi et al, 2005). Although we have not measured the TCH in the hippocampus, studies by Cutler et al (2004) have documented increased TCH in old mice at 25 months of age, and have related the increase to similar situations of oxidative stress involving activation of sphingomyelinases resulting in ceramide production and accumulation of TCH, and have shown that a-tocopherol is effective in inhibiting the enzymes.…”
Section: Discussionsupporting
confidence: 54%
“…The present results on increased LDL-C/TG and LDL-C/ HDL-C ratios in animals exposed to cold are indicative of LDL oxidation in vivo with the former ratio being suggested as an important predictor of LDL oxidation (Brizzi et al, 2005). Although we have not measured the TCH in the hippocampus, studies by Cutler et al (2004) have documented increased TCH in old mice at 25 months of age, and have related the increase to similar situations of oxidative stress involving activation of sphingomyelinases resulting in ceramide production and accumulation of TCH, and have shown that a-tocopherol is effective in inhibiting the enzymes.…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, increased serum TG concentrations have been associated with decreased LDL-C, which becomes more susceptible to oxidative modification (Brizzi et al 2003). It is widely accepted that atherogenesis is initiated by oxidation of the lipids in LDL-C (Chen et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated that over-training, as occurred in the TL group, accelerated the breakdown of HP and increased aldehyde production. These observations are substantially important in explaining the adverse alterations on serum lipids (1,4). Lipid hydroperoxides give rise to a large variety of products, many of which react with TBA and with serum lipids (1).…”
Section: Methodsmentioning
confidence: 99%